Atlantoaxial Instability in Patients Older Than 70 Years: What Is the Outcome When Further Conservative Treatment Is Not an Option? - Scholz, Christoph; Klingler, Jan-Helge; Scheiwe, Christian; Naseri, Yashar; Masalha, Waseem; Hubbe, UIrich (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Objective We report on our experiences of navigated posterior C1–C2 spondylodesis in the elderly (≥ 70 years of age).Patients This retrospective cohort study evaluated all patients ≥ 70 years of age treated with navigated posterior spondylodesis C1-C2 (at the most to C3) from 2008 to 2015 with a minimum follow-up of 1 year. Minor and major complications within 30 days after surgery, patient outcome, and the rate of solid fusion in computed tomography were recorded. The follow-up over 1 year was conducted by outpatient examinations and via telephone interviews.Results Twenty-two patients with a mean age of 79.9 years (range: 71–91 years) were treated. Minor complications were mild pneumonia (18.2%), postoperative confusion (9.1%), and urinary tract infection (4.5%). Major complications were severe pneumonia (4.5%) and clinically asymptomatic vertebral artery injury (4.5%). The mortality rate was 13.6% (n = 3) within the first 30 days after surgery and 22.7% (n = 5) within 1 year. All deceased patients were > 85 years of age.Conclusion In our patient population, posterior spondylodesis was shown to be beneficial for patients > 70 years up to age ∼ 85 years. The mortality rate increased sharply in patients > 85 years. In these patients the indication for surgery should be critically evaluated.
Keywords: cervical spine; elderly; geriatric; spondylodesis; atlantoaxial instability